A historical job-exposure matrix for occupational exposure to diesel exhaust using elemental carbon as an indicator of exposure. Issue 6 (17th August 2020) - Plato, Nils; Lewné, Marie; Gustavsson, Per
Abstract: Any study of the long-term health effects of diesel exhaust exposure requires past exposure to be assessed. Few historical measurements of occupational exposure to elemental carbon (EC) are available, so past exposure must be assessed using models and judgments based on indirect data. A job-exposure matrix (JEM) for historical occupational exposure to diesel exhaust based on EC is presented. Past exposure to EC in occupations with a high exposure to diesel exhaust was assessed using an eight-step process. The assessments were based on technical specific data and NO2 -exposure data, and a current EC-exposure measurement program. Finally, group assessment was carried out by consensus. Temporal variations in exposure were assessed for different groups. The matrix was constructed to assess annual average EC exposure for 72 occupations between 1950 and 2004. EC exposure between 1950 and 2004 varied between 1 and 247 µg/m 3, for farmers in 2000 and miners in 1975 respectively, and was generally highest in the 1970s. The JEM allows lifetime diesel exhaust exposure intensity in 72 occupations to be assessed and used in epidemiological studies.